PENGARUH PEMERIKSAAN DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Mohammad, Indira; Saerang, David Paul Elia; Pangerapan, Sonny (Universitas Sam Ratulangi, 2017)
Tax revenues include receipt tax and customs and excise, became the backbone of the state budget. Achievement of the target of the tax over the years yet provide maximum results. As the parties directly involved in the procedure of tax collection tax officials (tax authorities) became one of the factors that affect tax revenues. This study aims to determine the effect of the tax assessment and tax collection to tax revenues. The sampling method using a saturation sampling consisting of 50 respondents in the Tax Office Pratama of Manado. This study uses a quantitative analysis using multiple regression method. The results showed that the variable tax audit and tax collection influence positive and significant the variable tax revenue.Keywords: Tax Audit, Tax Collection, Tax Revenue.